Evangelizing Korean Women and Gender in the Early Modern World The Power of Body and Text - Broomhall, Susan (Arc Humanities Press, 2023)
This monograph examines how Korean women and men came to engage with Catholic missions during Europe's late sixteenth and seventeenth centuries, a profoundly volatile period in East Asian history during which political, cultural, and social disruption created opportunities for new interactions in the region. It analyzes the nature of that engagement, as women and men became both subjects for, and agents of, catechizing practices. As their evangelization, experience of faith, proselytizing, and suffering were recorded in mission archives, the monograph explores contact between Catholic Christianity and Korean women in particular. Broomhall demonstrates how gender ideologies shaped interactions between missionary men and Korean women, and how women's experiences would come to be narrated, circulated, and memorialized.